Word of honor [large type] - Bridgeman, Hallee (Bridgeman, Hallee. Love and honor, 2023)
"FBI Special Agent Lynda Culter is investigating an ecoterrorist organization in the Alaskan wilderness when her partner is taken captive and murdered before her very eyes. The only person who can identify the key players, Lynda gets assigned to take part in a joint operation in Istanbul to take the organization down.As a woman in a Muslim country, she'll find it much easier to move around undetected with a fake husband. Unfortunately for her, the man assigned to play the role is none other than US Army weapons specialist Bill Sanders--the man who crushed her heart into a million pieces back in college.With a cargo bay's worth of hurt and baggage between them, these two consummate professionals must play their parts perfectly if they hope to stop those responsible for bombing oil pipelines, killing innocent civilians, and threatening to destabilize the oil markets. But love long buried has a way of resurfacing at the most inopportune times--and protecting Lynda has become Bill's primary focus"--